Dissecting Hofmeister Effects: Direct Anion–Amide Interactions Are Weaker than Cation–Amide Binding. Issue 28 (30th May 2016) - Balos, Vasileios; Kim, Heejae; Bonn, Mischa; Hunger, Johannes
Abstract: Whereas there is increasing evidence for ion‐induced protein destabilization through direct ion–protein interactions, the strength of the binding of anions to proteins relative to cation–protein binding has remained elusive. In this work, the rotational mobility of a model amide in aqueous solution was used as a reporter for the interactions of different anions with the amide group. Protein‐stabilizing salts such as KCl and KNO3 do not affect the rotational mobility of the amide. Conversely, protein denaturants such as KSCN and KI markedly reduce the orientational freedom of the amide group. Thus these results provide evidence for a direct denaturation mechanism through ion–protein interactions. Comparing the present findings with results for cations shows that in contrast to common belief, anion–amide binding is weaker than cation–amide binding. Abstract : Negative vibes : Anions interact directly with amide groups, and the interaction strength follows the direct Hofmeister series. However, the binding of anions to the amide group is weaker than that of comparable monovalent cations.